A dominação masculina de Pierre Bourdieu: críticas e reflexões a partir da psicologia analítica - Lazdan, Alessandra Munhoz [UNESP]; Reina, Fabio Tadeu [UNESP]; Muzzeti, Luci Regina [UNESP]; Ribeiro, Paulo Rennes Marçal [UNESP] (My University, 2014)
This bibliographical article aimed to analyze the work Masculine domination of Pierre Bourdieu, considering the concepts of Analytical Psychology from C. G. Jung. Among other issues, this psychological theory is based on the analysis of the masculine and feminine principles in order to bring a different apparatus for discussion of the ideas brought by Bourdieu that involves masculine domination. The Analytical Psychology concepts understand this domination from the patriarchal view of society, according to Bourdieu in submission question that this culture imposes on women. However, there were counterpoints regarding the quality and validation of female reference that Bourdieu’s theory seems to disqualify. Among the permanencies and changes of the structures that reproduce the masculine order, both theories show agreement with updates regarding the patriarchal structure.

O presente artigo, de cunho bibliográfico, teve como objetivo fazer uma reflexão da obra A dominação masculina de Pierre Bourdieu a partir dos conceitos da Psicologia Analítica de C. G. Jung. Esta corrente da Psicologia fundamenta-se, entre outras questões, na análise dos princípios masculino e feminino, trazendo um aparato diferenciado para a discussão das ideias trazidas por Bourdieu que envolvem a dominação masculina. A leitura da Psicologia Analítica compreende a questão desta dominação a partir da visão patriarcal da sociedade, corroborando com Bourdieu na questão da submissão que esta cultura impõe à mulher. No entanto, houve contrapontos no tocante à qualidade e validação do referencial feminino, que a teoria bourdieuniana parece desqualificar. Entre as permanências e mudanças das estruturas que reproduzem a ordem masculina, ambas as teorias se mostram concordantes com as atualizações referentes à estrutura patriarcal.
Masculine domination of Pierre Bourdieu: critical and analyses from the analytical psychology
Keywords: Male; Psychology; Sociology; Masculino; Psicologia; Sociologia